4CPS-075 Persistence and cost analysis of secukinumab in patients with psoriatic arthritis, ankylosing spondylitis and psoriasis. Issue 1 (23rd March 2023) - Sanchez, R; Almiñana, M; Cortell, C; Garcia, A; Anton, M; Jimenez, A; Corpa, B
Abstract : Background and Importance: We know that the lack of persistence of the treatment affects its efficacy and can lead to an increase in the dose, which triggers an increase in risk and cost. Knowing the persistence of treatment with secukinumab in psoriatic arthritis (PsA), ankylosing spondylitis (AS) and psoriasis, could lead to new lines of research that compare the different therapeutic alternatives for these pathologies based on the cost per persistent treatment. Aim and Objectives: To determine the persistence of treatment with secukinumab and the cost of persistent treatment in its approved indications: PsA, AS and psoriasis. Material and Methods: Descriptive, retrospective observational study, which included adult patients with PsA, AS and psoriasis treated with secukinumab between November 2017 and August 2021. The demographic variables of age and sex were considered. The main variables were the persistence of secukinumab treatment and the annual cost per persistent treatment. Treatment persistence was analysed using the Kaplan-Meier test for each indication. The cost per persistent treatment was calculated based on the probability of persistence, which was estimated with the area under the curve for each of the three curves obtained in the Kaplan-Meier analysis. The secondary variables collected were diagnosis, duration and interruption of secukinumab treatment and previous lines of treatment. Results: We included 138 patients with a mean age of 52.2 ± 13.9 years, of whom 67 (48.6%) were women. The mean persistence of secukinumab treatment in PsA was 36.5 (95% CI 30.7-42.2) months, for AS it was 39.7 (95% CI 34.3-45.2) months and in psoriasis it was 40.4 (95% CI 35.1-45.7) months. A relationship between age, gender, indication, and line of treatment with secukinumab persistence could not be established. Median persistence was not reached for any of the three diagnoses. The annual cost per persistent treatment, calculated based on the probability of persistence, was €11, 064 for PsA, €8, 183 for AS, and €15, 420 for psoriasis. Conclusion and Relevance: Mean secukinumab persistence was higher for psoriasis compared to PsA and AS (p>0.05). The highest annual cost per persistent treatment was for psoriasis. More studies with real-life data and larger sample sizes are needed to establish the factors that play a key role in the persistence of secukinumab treatment. References and/or Acknowledgements: Conflict of Interest: No conflict of interest